Steamed Panax notoginseng and its Saponins Inhibit the Migration and Induce the Apoptosis of Neutrophils in a Zebrafish Tail-Fin Amputation Model - Xiong, Yin; Halima, Mahmoud; Che, Xiaoyan; Zhang, Yiming; Schaaf, Marcel J. M.; Li, Minghui; Gao, Min; Guo, Liqun; Huang, Yan; Cui, Xiuming; Wang, Mei (Frontiers in Pharmacology, 2022)
Panax notoginseng (PN) is a Chinese medicinal herb that is traditionally used to treat inflammation and immune-related diseases. Its major active constituents are saponins, the types and levels of which can be changed in the process of steaming. These differences in saponins are causally relevant to the differences in the therapeutic efficacies of raw and steamed PN. In this study, we have prepared the extracts of steamed PN (SPNE) with 70% ethanol and investigated their immunomodulatory effect using a zebrafish tail-fin amputation model. A fingerprint-effect relationship analysis was performed to uncover active constituents of SPNE samples related to the inhibitory effect on neutrophil number. The results showed that SPNE significantly inhibited the neutrophil number at the amputation site of zebrafish larvae. And SPNE extracts steamed at higher temperatures and for longer time periods showed a stronger inhibitory effect. Ginsenosides Rh1, Rk3, Rh4, 20(S)-Rg3, and 20(R)-Rg3, of which the levels were increased along with the duration of steaming, were found to be the major active constituents contributing to the neutrophil-inhibiting effect of SPNE. By additionally investigating the number of neutrophils in the entire tail of zebrafish larvae and performing TUNEL assays, we found that the decreased number of neutrophils at the amputation site was due to both the inhibition of their migration and apoptosis-inducing effects of the ginsenosides in SPNE on neutrophils. Among them, Rh1 and 20(R)-Rg3 did not affect the number of neutrophils at the entire tail, suggesting that they only inhibit the migration of neutrophils. In contrast, ginsenosides Rk3, Rh4, 20(S)-Rg3, and SPNE did not only inhibit the migration of neutrophils but also promoted neutrophilic cell death. In conclusion, this study sheds light on how SPNE, in particular the ginsenosides it contains, plays a role in immune modulation.